Hadith of Fitanand Malaḥimin the canonical hadith collections: Its concept and main themes - Yasir Ramlee (Universiti Sains Islam Malaysia, 2025)
Hadiths related to Fitan (trials) and malāḥim (fierce battles) constitute a significant part of the Prophetic tradition, as they address major events expected to occur at the end of times including conflicts, social upheavals, and the signs of the Hour. This study aims to explore the concepts of fitanand malāḥimin the Prophetic hadiths and to analyses their main themes as presented in the canonical hadith collections such as Ṣaḥīḥal-Bukhārī, Sahih Muslim, Sunan Abi Dawud, and others. Employing both inductive and analytical methods, the study extracts the key meanings of these hadiths and relates them to both historical contexts and contemporary realities.The findings reveal that these hadiths comprise a collection of Prophetic narrations discussing the various trials individuals may encounter in their lives, whether personal or collective. The hadiths of fitanand malāḥim can be grouped into four main themes: (1) the depiction of events that will occur before the end of the world, (2) the establishment of Islamic creed in the hearts of believers, (3) the assertion that tribulations will affect all human beings, and (4) Prophetic guidance on how to face tribulations with Huda (divine guidance) and Taqwa (piety).This study contributes to a deeper understanding of the hadiths concerning fitanand malāḥimas documented in the canonical hadith collections, while also highlighting the dynamic and far-reaching scope of these narrations.